The Relationship between Conflict Management and Schools Effectiveness in Sunthorn Phu Education Network under Rayong Primary Educational Service Area office 2 - Chuntuy, Panudda; Sinjindawong, Sirinthorn (Journal of Roi Et Rajabhat University, 2020)
The research aimed to study 1) level of conflict management, 2) level of effectiveness, and 3) relationship between conflict management and effectiveness of schools in Sunthorn Phu Education Network under Rayong Primary Educational Service Area office 2. The population in this study included 131 primary schools administrators and teachers in Sunthorn Phu Education Network under Rayong Primary Educational Service Area office 2 in 2018 academic year. The research instrument was a questionnaire developed by the researcher. Statistic for data-analysis were percentage, mean, standard deviation and Pearson’s correlation. The results showed that 1) conflict management of schools in Sunthorn Phu Education Network under Rayong Primary Educational Service Area office 2 was at the moderate level ( = 3.38, = 0.88) as a whole, 2) effectiveness of schools in Sunthorn Phu Education Network under Rayong Primary Educational Service Area office 2 was at the high level ( = 4.12, =0.52), as a whole and in each aspect and 3) relationship between the conflict management and effectiveness of schools in Sunthorn Phu Education Network under Rayong Primary Educational Service Area office 2 had the correlation at the moderate level with significantly different at the statistical level of .01.